Yield Response to Planting Date Among Soybean Maturity Groups for Irrigated Production in the US Midsouth. Issue 2 (1st March 2016) - Salmerón, Montserrat; Gbur, Edward E.; Bourland, Fred M.; Buehring, Normie W.; Earnest, Larry; Fritschi, Felix B.; Golden, Bobby R.; Hathcoat, Daniel; Lofton, Josh; McClure, Angela Thompson; Miller, Travis D.; Neely, Clark; et al.
Abstract : Planting date is one of the main factors affecting soybean (Glycine max [L.] Merr.) yield. Environmental conditions in the US Midsouth allow for planting dates from late March through early July, and maturity groups (MGs) ranging from 3 to 6. However, the complexity of interactions among planting date, MG, and the environment makes the selection of an optimum MG cultivar difficult. A regional 3‐yr study, conducted at eight locations with latitudes ranging from 30.6 to 38.9°N, planting dates ranging from late March to early July, and MGs 3 to 6, was used to examine the relationship between relative yield and planting day. The data indicated that yield was dependent on the location and MG choice. There was a quadratic response of relative yield to planting day in six out of the eight locations studied for MG 3 cultivars, and in five locations for MG 4 cultivars. On the other hand, MG 5 and 6 cultivars were more likely to have a negative linear relationship, with a quadratic response in only two of the eight locations. Optimum planting dates that maximized yield were dependent on the location and MG combination and ranged from 22 March to 17 May. Delaying planting dates from mid May to early June reduced yields by 0.09 to 1.69% per day, with the rate of decline greatest at the southern‐most locations. Overall, MG 4 cultivars maximized yield or were not statistically different from the highest yielding MG at most locations and planting dates.